Pendelegasian Undang-Undang Pajak Mengenai Tarif Tertinggi ke Peraturan Pemerintah Menjadi Tarif Terendah Dihubungkan Dengan Teori Hirarki - Nurlaeli, Suci (Lex Jurnalica, 2024)
In essence, tax arrangements are regulated by law. However, Article 17 paragraph (2) of Law Number 7 of 2021 concerning Harmonization of Tax Regulations regulates the delegation of regulations for changes in tax rates to Government Regulations. Appropriately, these substantial provisions cannot be regulated by Government Regulations because Government Regulations have a lower position than Laws so that Government Regulations only regulate technical provisions of Laws. Therefore, this research was conducted using normative juridical methods to determine the position of laws and government regulations in the hierarchy of statutory regulations, as well as to determine the validity of the delegation of tax rate regulations in Article 17 paragraph (2) based on hierarchy theory. The results of this research are that delegation is valid and appropriate when linked to hierarchy theory. This is because there are requirements to be able to make changes to tax rates in Government Regulations, namely by involving the community represented by the DPR in preparing the RAPBN. Without mutual agreement with the DPR, changes to tax rates cannot be made by the government into Government Regulations.